Pro-Environmental Behavior Learning by Using a Mini Research Project and Its Impact on Problem Solving Abilities - Anggereini, Evita; Yelianti, Upik; Hermaya, Intan (Jurnal Pendidikan Indonesia, 2023)
Currently students are expected to have the ability to solve environmental problems, especially in everyday life, which is known as pro-environmental behavior or actions. One of the strategies in teaching students' problem solving abilities is by learning mini research to solve problems in the surrounding environment, especially in the scope of biology. This study aims to analyze the effect of pro-environmental behavior learning by using a mini research project on problem solving abilities and how much influence it has on students in Senior High School. The research method used is associative quantitative with comparative type. The population in this study were students of ten grade Senior High School in science class and from this population a sample would be taken using simple random sampling technique, with a total sample of 96 students from three classes. This research procedure includes the preparation stage, implementation stage and data analysis stage. The research instruments used were in the form of question sheets and questionnaires. Based on the data obtained, the average score of the highest problem solving value is 74.7 and the lowest is 68.9. Then it can be concluded that there is an influence from the use of learning with a mini research project on problem solving abilities. The implication of this research is that it can be used by teaching staff as a reference in using the integrated mini research learning model of pro environmental behavior to improve students' problem solving abilities.